Cross-Linguistic Analysis of Vietnamese and English with Implications for Vietnamese Language Acquisition and Maintenance in the United States - Giang Tang (Journal of Southeast Asian American Education and Advancement, 2007)
Two overall goals of this paper are a) to provide a linguistic basis for promoting first language maintenance of Vietnamese in a larger United States context and b) to stimulate future research in language acquisition of Vietnamese-English speakers. This paper is divided into three sections. Section 1 discusses previous studies on first language (L1) maintenance among Vietnamese Americans. Section 2 presents a cross-linguistic comparison of Vietnamese and English across speech-sound, word, and grammatical language levels. A cross-linguistic analysis may help educators better understand speaking patterns of Vietnamese American students. Based on this cross-linguistic comparison, Section 3 presents potential bi-directional interactions between Vietnamese and English within an individual speaker. These predictions are intended to provide a framework for future empirical studies related to bilingual development.